CORRECCIÓN ATMOSFÉRICA DE LAS IMÁGENES VISIBLES DEL SENSOR AVHRR – NOAA USANDO LOS MODELOS 5S Y SMAC - Rojas Acuña, Joel (2006)
In this work has been implemented the model of atmospheric correction denominated “Simplified Method for the Atmospheric Correction” (SMAC). It consists of determining the relation between the reflectance calculated on the top of the atmosphere and the reflectance calculated at the surface of the soil using mathematical algorithms of radiative transference, Rayleigh`s scattering, scattering of aerosols, and others. One has compared the values of reflectance in the top of the atmosphere and the reflectance of the surface of the ground, obtaining like result a linear relation of the these two amounts with a value of he slope equal to 1.44. The value of slope greater than 1 indicates that an acceptable atmospheric correction has been made. In order to validate the model has been obtained the values of the reflectance of the surface of the ground using the 5S model, obtaining a coefficient of correlation 0.99. With this it is tried to help to obtain more exact geophysical parameters for those than it is desired to obtain from satellite images.